The effects of semaphorin 3A in bone and cartilage metabolism: fundamental mechanism and clinical potential - Wu, KaiLe; Huang, Donghua; Huang, Xin (Frontiers in Cell and Developmental Biology, 2023)
Semaphorin 3A (Sema3A) is a neuroinformatic protein molecule with widespread expression across various tissues and organs. Recent investigations have unveiled its pivotal role in the skeletal system, primarily through its binding interactions with two co-receptors, neuropilin-1 (Nrp-1) and members of the plexin family. Prior research has confirmed the expression of Sema3A and its receptors in both osteocytes and chondrocytes. Beyond its expression patterns, Sema3A plays a multifaceted role in regulating bone and cartilage metabolism via employing diverse signaling pathways. Additionally, it engages in collaborative interactions with the immune and nervous systems, contributing to the pathophysiological processes underlying a spectrum of bone and joint diseases. In this paper, we undertake a comprehensive review of recent research developments in this field. Our objective is to deepen the understanding of Sema3A within the context of skeletal physiology and pathology. Furthermore, we aim to furnish a valuable reference for potential therapeutic interventions in the realm of bone and joint diseases.